KAJIAN LANSKAP KAWASAN WISATA PANTAI TANJUNG BASTIAN SEBAGAI KAWASAN WISATA BUDAYA DI KEFAMENANU KABUPATEN TIMOR TENGAH UTARA - Niis, Maria Sofiana; Setyabudi, Irawan; Nuraini, Nuraini (Universitas Tribhuwana Tunggadewi, 2019)
Tanjung Bastian Beach has an important role for the development and Kefamenanu community in terms of the economic aspects of the beach, the socio-cultural and ecological aspects have the potential to bring benefits to the local community. But the beach is less attention from the government and surrounding communities. the condition of the beach is poorly maintained, has not been well ordered and the culture is increasingly extinct. In this research a study is needed to identify the area of cultural tourism. The results of the study of the development of the Tanjung Bastian coastal tourism area as a cultural tourism area will be useful in the management, preservation, and development and cultural potential. This analysis process uses a SWOT Analysis to find out more about the development of cultural tourism, as well as the possibilities that can be done relating to strengths, weaknesses, opportunities, and threats in the development of Cultural tourism. From the research results obtained several strategies from the SWOT matrix which are categorized into a number of strategies to develop Tanjung Bastian Beach Tourism area, namely the community must make Pokdarwis and develop local culture as cultural attractions, then the Government plays an active role in the tourist areas and provides facilities to support cultural activities on the Tanjung beach. Bastian, the Government cooperates with the local community, so that the community participates in protecting its nature and enhancing its social culture. Based on the results of a study of the cultural tourism area, it can be concluded that the Tanjung Bastian Beach is not in accordance with the criteria as a Cultural Tourism area. Pantai Tanjung Bastian mempunyai peranan penting bagi pembangunan dan masyarakat Kefamenanu ditinjau dari aspek ekonomi Pantai, sosial budaya dan aspek ekologi sangat berpotensi mengutungkan masyarakat setempat. Namun pantai tersebut kurang perhatian dari pemerintah dan masyarakat sekitar. kondisi pantai tidak terawat, belum tertata dengan baik dan kebudayaannya semakin punah. Dalam penelitian ini perlu diadakan suatu kajian untuk mengidentifikasi kawasan wisata budaya. Hasil kajian pengembangan kawasan wisata pantai Tanjung Bastian sebagai kawasan wisata budaya akan berguna dalam kegiatan pengelolaan, pelestarian, serta pengembangan dan potensi budaya. Proses analisis ini menggunakan Analisis SWOT untuk mengetahui lebih lanjut dari perkembangan wisata budaya, serta kemungkinan yang dapat dilakukan berkaitan dengan kekuatan, kelemahan, peluang, dan ancaman dalam pengembangan wisata Budaya. Dari hasil penelitian diperoleh beberapa strategi dari matriks SWOT yang dikategori menjadi beberapa strategi pengembangan kawasan Wisata Pantai Tanjung Bastian yaitu Masyarakat harus membuat pokdarwis dan mengembangkan budaya lokal sebagai atraksi budaya, kemudian Pemerintah berperan aktif akan daerah wisata dan menyediakan fasilitas untuk mendukung kegiatan budaya di pantai Tanjung Bastian, Pemerintah bekerja sama dengan masyarakat setempat, sehingga masyarakat ikut dalam menjaga alamnya serta meningkatkan sosial budaya. Berdasarkan hasil kajian dari kawasan wisata budaya dapat menyimpulkan bahwa Pantai Tanjung Bastian belum sesuai dengan kriteria sebagai kawasan Wisata Budaya.